Usefulness of cardiac computed tomography in transcatheter closure of atrial septal defect with amplatzer septal occluder - Jinyoung . Song; Yang Min . Kim; Toibayeva . Aigerim (Российский кардиологический журнал)
Background: Atrial septal defect (ASD) can be closed safely by transcatheter closure with an Amplatzer septal occluder (ASO) with cardiac computed tomography (CT) being used to image and evaluate the ASD. The purpose of this study was to evaluate the characteristics of Secundum ASD by CT and to determine whether cardiac CT is an alternative to balloon sizing. Methods and Results: Forty-four ASD cases were evaluated by cardiac CT. we measured the defect diameters and lengths of the rims. The patients were divided into two groups: not using a balloon sizing technique (group 1), and using a balloon sizing technique (group 2). Most ASD cases showed ellipsoid defects with 19,6±6,5 cm for the longest diameter and 15,5±5,3 for the shortest. Except for two patients, they had sufficient posterior-inferior rims. We observed that the ratios of the device size to the longest diameter and the ratios of the occluder area to the defect area measured on CT were significantly smaller in group 1 than those in group 2 (1,1±0,1 vs 1,3±0,2 and 1,6±0,3 vs 2,2±0,9). Conclusions: Cardiac CT is useful for evaluating ASDs for transcatheter closure with an ASO. It can allow the operator to select a smaller size device than when using a stretched balloon sizing technique.